Exploring resilience in family physicians working in primary health care in the Cape Metropole - Leigh Wagner; Michael K. Pather (AOSIS, 2019)
Background: Despite the high prevalence of burnout among doctors, studies have shown that some doctors who choose to remain in primary healthcare (PHC) survive, even thrive, despite stressful working conditions. The ability to be resilient may assist family physicians (FPs) to adapt successfully to the relatively new challenges they are faced with. This research seeks to explore resilience through reflection on the lived experiences of FPs who have been working in PHC. Aim: To explore the resilience of FPs working in PHC in the Cape Metropole. Setting: The study was conducted among FPs in PHC in the Cape Town metropole, Western Cape province, South Africa. Methods: A phenomenological qualitative study involved interviewing 13 purposefully selected FPs working in the public sector PHC in the Cape Metropole. Data were analysed using the framework method. Results: The mean resilience scale was moderate. Six key aspects of resilience were identified: having a sense of purpose, 'silver lining' thinking, having several roles with autonomy, skilful leadership, having a support network and self-care. Conclusion: The aspects that contribute to FP resilience are multi-faceted. It entails having a sense of purpose, 'silver lining' thinking, having several roles with autonomy, skilful leadership, having a support network and valuing self-care. Our exploration of resilience in FPs in the Cape Metropole corroborates the findings of previous studies. To ensure physician wellness and improved patient outcomes, we recommend that individual and organisational strategies should be implemented in the absence of long-term policy changes.